2018
DOI: 10.1016/j.tmaid.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of emerging respiratory viruses at the Hajj and possible coinfection with Streptococcus pneumoniae

Abstract: Well conducted multinational follow-up studies using the same methodology of testing are necessary for accurate surveillance of respiratory viral infections among Hajj pilgrims. Post-Hajj cohort studies would further evaluate the impact of the Hajj on the acquisition of respiratory viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 78 publications
1
41
1
Order By: Relevance
“…Ebola, MERSCoV, Alkhumra viral haemorrhagic fever, and Rift Valley fever have high outbreak potential during Hajj. 10,76,77 Although the threat of coronaviruses (MERSCoV and severe acute respiratory syndromerelated coronavirus) with epidemic potential remains, [77][78][79][80][81] no cases of MERSCoV have yet been identified in pilgrims during Hajj or upon return to their home countries. 79 Other corona viruses identified at the Hajj include alphacoronavirus and betacoronavirus, of which the 229E strain is most common cause of upper respiratory tract illnesses.…”
Section: Infectious Diseases At the Hajjmentioning
confidence: 99%
See 1 more Smart Citation
“…Ebola, MERSCoV, Alkhumra viral haemorrhagic fever, and Rift Valley fever have high outbreak potential during Hajj. 10,76,77 Although the threat of coronaviruses (MERSCoV and severe acute respiratory syndromerelated coronavirus) with epidemic potential remains, [77][78][79][80][81] no cases of MERSCoV have yet been identified in pilgrims during Hajj or upon return to their home countries. 79 Other corona viruses identified at the Hajj include alphacoronavirus and betacoronavirus, of which the 229E strain is most common cause of upper respiratory tract illnesses.…”
Section: Infectious Diseases At the Hajjmentioning
confidence: 99%
“…79 Other corona viruses identified at the Hajj include alphacoronavirus and betacoronavirus, of which the 229E strain is most common cause of upper respiratory tract illnesses. 82 A systematic review of 31 studies on the prevalence of respiratory viruses in Hajj pilgrims 76 showed influenza, rhinovirus, and parainfluenza continue to be the most common viral infections among pilgrims. At the 2016 Hajj, a study 83 of 266 pilgrims admitted to hospitals with community acquired pneumonia showed that 96 (36%) cases had diabetes, 26 (10%) were smokers, and 108 (45%) cases required intensive care.…”
Section: Infectious Diseases At the Hajjmentioning
confidence: 99%
“…Influenza vaccine decreases development of influenza like-illness among pilgrims [49]. The compliance with influenza vaccination varies from 7.1% to 100% with an overall compliance of 96.3% [49][50][51]. The occurrence of the mismatch between vaccine and circulating influenza strains occur frequently and affect the Hajj pilgrims [52].…”
Section: Influenza Vaccinationsmentioning
confidence: 99%
“…Cohort studies conducted in populations of pilgrims originating from different countries reported that a substantial proportion of pilgrims suffer from respiratory symptoms during their stay in Saudi Arabia [6]. On the other hand, numerous PCR-based studies have demonstrated the frequent acquisition of respiratory viruses following participation in Hajj [7,8]. Fortunately, SARS-CoV and MERS-Cov did not affect Hajj pilgrims so far [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, SARS-CoV and MERS-Cov did not affect Hajj pilgrims so far [9,10]. However, rhinovirus, non-MERS coronaviruses and influenza viruses are commonly isolated from both asymptomatic returning pilgrims and pilgrims with acute respiratory symptoms [7,8]. Due to the lack of detailed clinical information in many Hajj studies and the high https://doi.org/10.1016/j.tmaid.2019.03.003 Received 20 December 2018; Received in revised form 2 March 2019; Accepted 5 March 2019 sensitivity of PCR tools, the contribution of viruses to observed symptoms remains unknown.…”
Section: Introductionmentioning
confidence: 99%